Identifying barriers and opportunities in the deployment of the residential photovoltaic prosumer segment in Chile. (June 2021) - Osorio-Aravena, Juan Carlos; de la Casa, Juan; Töfflinger, Jan Amaru; Muñoz-Cerón, Emilio
Highlights: Updated overview of the residential PV prosumer market's status in Chile is given. High investment costs and low income per household are the main deployment barriers. Up to double the levelized cost of electricity differences are reached across Chile. Net-billing scheme does not ensure the profitability of residential PV systems. Options without compromising the national budget improve the scenario for the RPVP. Abstract: Photovoltaic (PV) prosumers can play a significant role in the transition toward sustainable cities. However, the implementation of more effective policies which accelerate the deployment of this market is needed. In this study, after an overview of the residential PV prosumer (RPVP) market's status in Chile, critical parameters that can speed-up the deployment of this segment through policy decisions were identified. Considering the local conditions of each regional capital in Chile, the segment is analyzed with widely-used econometric techniques to evaluate the residential PV systems feasibility empirically. The results show that the Chilean regulatory framework is insufficient for exploiting the potential of the RPVP. Without effective policy instruments, high investment costs and low income per household are the main barriers in the deployment of the segment in this country. Therefore, suitable promotion energy policies, regulatory changes, and financing options can accelerate the deployment without majorly impacting on the national budget. This would let citizens help accelerate decarbonization through a more decentralized and democratic energy transition, gaining socio-economic and socio-environmental benefits, based on solar PV technology.